Annexin A1 protein attenuates cyclosporine-induced renal hemodynamics changes and macrophage infiltration in rats - Araujo, Leandro Pires; Truzzi, Renata Ramos [UNESP]; Florido Mendes, Gloria Elisa; Mendes Luz, Marcus Alexandre; Burdmann, Emmanuel A.; Oliani, Sonia Maria [UNESP] (Springer Basel Ag, 2012)
Cyclosporine (CsA) remains an important immunosuppressant for transplantation and for treatment of autoimmune diseases. The most troublesome side effect of CsA is renal injury. Acute CsA-induced nephrotoxicity is characterized by reduced renal blood flow (RBF) and glomerular filtration rate (GFR) due to afferent arteriole vasoconstriction. Annexin A1 (ANXA1) is a potent anti-inflammatory protein with protective effect in renal ischemia/reperfusion injury. Here we study the effects of ANXA1 treatment in an experimental model of acute CsA nephrotoxicity.Salt-depleted rats were randomized to treatment with VH (vehicles 1 mL/kg body weight/day), ANXA1 (Ac2-26 peptide 1 mg/kg body weight/day intraperitoneally), CsA (20 mg/kg body weight/day subcutaneously) and CsA + ANXA1 (combination) for seven days. We compared renal function and hemodynamics, renal histopathology, renal tissue macrophage infiltration and renal ANXA1 expression between the four groups.CsA significantly impaired GFR and RBF, caused tubular dilation and macrophage infiltration and increased ANXA1 renal tissue expression. Treatment with ANXA1 attenuated CSA-induced hemodynamic changes, tubular injury and macrophage infiltration.ANXA1 treatment attenuated renal hemodynamic injury and inflammation in an acute CsA nephrotoxicity model.
Keywords: Acute renal injury; Annexin A1; Cyclosporine nephrotoxicity; Immunosuppression; Inflammation